2021
DOI: 10.1007/s11356-021-17607-y
|View full text |Cite|
|
Sign up to set email alerts
|

Levels and risks of surface contamination by thirteen antineoplastic drugs in the Czech and Slovak hospitals and pharmacies

Abstract: The consumption of hazardous antineoplastic drugs (ADs) used in anticancer chemotherapies is steadily increasing representing thus risks to both human health and the environment. Hospitals may serve as a contamination source, and pharmacists preparing the antineoplastic drugs (ADs) as well as nurses administering chemotherapy and caring for oncology patients are among the healthcare professionals being highly exposed. Here, we present the results of systematic monitoring (2018-2020) of surface contamination by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Dolezalova et al described the 2018–2020 contamination with 13 antineoplastic drugs in 24 centers across Czech Republic and Slovak Republic, and they found 5-fluorouracil, cyclophosphamide, and platinum to be the most frequent drugs on surfaces. 23 Sottani et al reported the 2016–2021 contamination in nine Italian centers with four drugs and found gemcitabine to be the most frequently measured on surfaces, followed by cyclophosphamide and platinum. 11 This group also indicated that while 5-fluorouracil was the less frequent drug on surfaces, its concentration was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Dolezalova et al described the 2018–2020 contamination with 13 antineoplastic drugs in 24 centers across Czech Republic and Slovak Republic, and they found 5-fluorouracil, cyclophosphamide, and platinum to be the most frequent drugs on surfaces. 23 Sottani et al reported the 2016–2021 contamination in nine Italian centers with four drugs and found gemcitabine to be the most frequently measured on surfaces, followed by cyclophosphamide and platinum. 11 This group also indicated that while 5-fluorouracil was the less frequent drug on surfaces, its concentration was the highest.…”
Section: Discussionmentioning
confidence: 99%
“…Manual handling or automatic manufacturing of preparations, infusion of treatment, patients care waste management, and cleaning procedures are all steps during which the risk of contamination is present. Healthcare workers might be exposed when aerosols, leaking or spillage are generated, or when they come in contact with contaminated surfaces during the manufacturing of the preparations, infusion procedure disposal of waste, or cleaning (armchair, toilets, floor or bedding) (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: State Of Artmentioning
confidence: 99%
“…Regular monitoring of environmental contamination has been carried out for several years in German ( 23 ), Italian ( 24 ), Czechoslovakian ( 19 ), Canadian ( 20 ) or American hospitals ( 21 ). These monitoring have shown that the risk of healthcare exposure is not systematically related to the level of environmental contamination or to the activity of the chemotherapy process but more to the practices and awareness of healthcare workers.…”
Section: State Of Artmentioning
confidence: 99%
“…However, other processes in handling of ADs are often less controlled and may lead to serious occupational exposures of nurses as well as sanitary staff (cleaning of contaminated floors or desktops/tables, handling and washing of contaminated beddings). Recently, exposures to ADs in home care settings have also been documented ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of contamination in workplaces is an important tool in risk management of these hazardous compounds ( 3 , 10 , 12 , 19 22 ), and the standardized wipe sampling of the surfaces is the most broadly used approach to detect contamination by ADs ( 3 ). Monitoring results allow to prioritize hot spots, identify major sources, routes of release of ADs during handling, compare situations among health care facilities and positive results often trigger implementation of remedial, and preventive measures ( 3 ).…”
Section: Introductionmentioning
confidence: 99%